PENGUKURAN KEPUASAN KERJA GURU DARI PERSPEKTIF KOMPETENSI MANAJERIAL KEPALA SEKOLAH DAN EFEKTIVITAS MANAJEMEN KEPEGAWAIAN - Ahmad Aziz Faozi (stit-islamic-village, 2022)
The success of an educational institution (school) is largely determined by the success of the principal in managing the teaching staff itself. Staffing management (teachers) in schools aims to utilize the teaching staff effectively and efficiently to achieve optimal results. In terms of staffing management must be supported by the principal who has managerial expertise in managing an educational institution, in other words good management of staffing will be supported by managerial skills of qualified principals. The formulation of the problem in this study are 1) Is there an effect of the effectiveness of staffing management on teacher job satisfaction in MTs Negeri 2 Tangerang? 2) Is there an effect of the principal's managerial competence on teacher job satisfaction in MTs Negeri 2 Tangerang? 3) Is there an effect on the effectiveness of staffing management and school principals' managerial competencies on teacher job satisfaction in MTs Negeri 2 Tangerang? The objectives to be achieved are 1) To find out whether there is an effect of the effectiveness of staffing management on teacher job satisfaction in MTs Negeri 2 Tangerang. 2) To find out whether there is an influence on the principal's managerial competence on teacher job satisfaction in MTs Negeri 2 Tangerang 3) To find out whether there is an effect on the effectiveness of staffing management and the principal's managerial competence on teacher job satisfaction in MTs Negeri 2 Tangerang. The research method used is a quantitative method using correlation analysis and regression. The population is 44 teachers. Because the total population is below all, then the total population is taken. Data before testing the hypothesis using several steps and procedures namely the validity test, reliability test, normality test, homogeneity test. And then the significance test, correlation test, and the coefficient of determination test. The first hypothesis results show there is an effect of the effectiveness of staffing management on teacher job satisfaction by 69.72%. The second hypothesis results show there is an influence of principals' managerial competence on teacher job satisfaction by 21.96%, and the results of the third hypothesis show that there is an effect of the effectiveness of staffing management and principals managerial competence on teacher job satisfaction by 54.46%. Improved teacher job satisfaction can be done through increasing the effectiveness of staffing management and managerial competencies of school principals.